The Dynamics of Women and Political Heritage in Yogyakarta: A Critical Reflection in Welcoming the Next Leader - Theresia Octastefani; Nur Azizah (Muwazah, 2019)
Yogyakarta Special Region (DIY) is an area still retains a strong cultural heritage, ranging from customs of Javanese-Islamic culture and Mataram Sultanate system. DIY becomes the only province that has a special authority to institutionalize the administration of government by placing the roles and responsibilities of the Ngayogyakarta Hadiningrat Sultanate and Kadipaten Pakualaman in filling the positions of provincial leaders. This process was legitimized by Indonesian Law No. 13 of 2012 about Special Administrative Status for Yogyakarta. But over time, polemics have emerged since Sri Sultan Hamengku Buwono X issued Sabda Raja and Dawuh Raja who reaped pros-cons and were clashed with the royal tradition’s values from generation to generation. Based on these realities, it becomes interesting to discuss about the dynamics of women and politics of heritage in DIY as a critical reflection in welcoming the next leader. On the one side, the system of the Javanese-Islamic Mataram Sultanate as a cultural heritage must be maintained. But on the other side, the aspect of modernity through the struggle for gender equality also opens the opportunity for Indonesian women are also capable of being and have become capable democratic leaders in the 21st Century.